2020
DOI: 10.3390/asi3040050
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Innovation Based BPR Regime—A Factors Analysis

Abstract: Sri Lankan public services have a lingering colonial legacy, and there have been several efforts since the country’s independence to break away from the restraints of the past to align them with modern times and expectations. The drive for modernization of public services passed through several phases of experimentation without much success in the past. A significant attempt at the modernization of public services was made in the first decade of this millennium; we now notice substantial changes in public serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…It is crucial to understand how to plan and adopt appropriate service innovations to effectively assist the sustainable operation and management of the company. Research showed that IOI innovation is a useful tool to enhance business performance [21]. My results agree with those of this previous study, suggesting that although both input and output innovation are significantly correlated, some inside decisions have more significant effects on the service innovation of the business.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is crucial to understand how to plan and adopt appropriate service innovations to effectively assist the sustainable operation and management of the company. Research showed that IOI innovation is a useful tool to enhance business performance [21]. My results agree with those of this previous study, suggesting that although both input and output innovation are significantly correlated, some inside decisions have more significant effects on the service innovation of the business.…”
Section: Discussionsupporting
confidence: 90%
“…Research has shown that managerial innovations result in alterations to existing working patterns, systems, procedures, and style, resulting in efficiency and effectiveness in the delivery of services. Two critical areas were shown to provide efficient service in performance: the fundamental rethinking of the definition of service and the radical redesign of business processes [21]. In order to improve a service, remarkable innovations that break away from the old methods are needed and newer ones must be adopted.…”
Section: S-d Logic In Economic Value For Service Innovationmentioning
confidence: 99%
“…Correlation research design is used to discover the relationship between two concepts. It is measured by a five—point scale ranging from 1 to 5, where “1 = strongly disagree, 2 = Disagree, 3 = neither disagree nor agree, 4 = Agree and 5 = strongly agree” ( Jehan & Elapatha, 2020 ). Its most important features are simple to build and reliable, participants can read and complete it easily and more viable for measuring the good results.…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers presented relationship study results between BPR and OC individual factors without a depth in effect or correlation of OC factors. [47][48][49] identified seven factors that are important to the success of BPR. Those factors are teamwork and quality culture, quality management system, effective change management, less bureaucracy, IT, project management and financial resources.…”
Section: Bpr Factorsmentioning
confidence: 99%